PENGARUH CITRA DAN PROMOSI TERHADAP KEPUASAN PELANGGAN SERTA DAMPAKNYA TERHADAP LOYALITAS PELANGGAN (STUDI PADA PELANGGAN SUPERMARKET CARREFOUR DI SEMARANG) - Tjahjaningsih, Endang (Proceeding Fakultas Ekonomi, 2013)
This research aims to develop and test empirical model of development customer loyalty on the basis of image and promotion. The research was conducted at Customer of Carrefour Supermarket in Semarang. The empirical test model used was regression analysis by using some software, such as: SPSS 16.0 and Microsoft Excel version. 2007. The sample size of the study was 100 Customer of Carrefour Supermarket in Semarang. The results showed that image affect positively towards customer satisfaction, and promotion affect positively towards customer satisfaction. Image, promotion, and customer satisfaction affect positively towards customer loyalty. Furthermore, mediating effect of customer satisfaction apply to image effects on customer loyalty. Customer satisfaction serves as a mediating variable between the variable image on customer loyalty. Mediating effect of customer satisfaction apply for promotion effect on customer loyalty. Customer satisfaction serves as a mediating variable between promotional variables on customer loyalty. This study contributes to the Resources-Based Theory, and Market Based Views. Limitation, theoretical implications, and managerial implications are also discussed in this study. Keywords: image, promotion, customer satisfaction, customer loyalty